Bone marrow uptake of ferumoxytol: A preliminary study in healthy human subjects. Issue 6 (10th October 2013) - Storey, Pippa; Arbini, Arnaldo A.
Abstract : Purpose: To characterize the uptake and elimination of ferumoxytol, an ultrasmall superparamagnetic iron oxide (USPIO) agent, in bone marrow of healthy human subjects. Materials and Methods: Four men and two postmenopausal women, aged 22 to 57 years, were prospectively included. Simultaneous fat, water, and T 2 * mapping of the proximal femora was performed at 1.5 Tesla using a three‐dimensional multiple gradient echo sequence. After baseline imaging, ferumoxytol (Feraheme/Rienso) was injected intravenously at a dose of 5 mg Fe/kg body weight. Imaging was repeated at 3 days, 1 month, 3 months, and 5 months after administration. Results: Imaging at 3 days revealed large increases in R 2 * ( = 1 / T 2 * ) in hematopoietic marrow and lower average responses in fatty marrow, consistent with macrophage‐specific uptake. However, certain regions of the diaphysis exhibited substantial R 2 * enhancement despite having very high fat content. This suggests the persistence of residual marrow stroma following adipose conversion, and may reflect the ability of diaphyseal marrow to adapt dynamically to fluctuating demand for hematopoiesis. Follow‐up imaging demonstrated almost complete R 2 * recovery within 3 months. Conclusion: The observed R 2 * enhancement characteristics support applications for ferumoxytol in distinguishing normal or hypercellular marrow from neoplasms, infection and inflammation. Further studies are warranted in specific patient populations.J. Magn. Reson. Imaging 2014;39:1401–1410 . ©2013 Wiley Periodicals, Inc.